Ensino de química orgânica para deficientes visuais empregando modelo molecular - Creppe, Carlos Henrique (2009)
This study was for the educational process more generally, by which members of a society are prepared to participate in social life. The correlation involves theoretical and practical aspects that must be articulated when it comes to teaching-learning process. For this study sought to individuals who have acquired visual impairment, focusing on the difficulties encountered, among them the absence of Tailored Materials (MDAs) to a better understanding of chemical concepts. Through an identification made in listing blind students and graduates enrolled in school in a public teaching institution in the modality Education for Youths and Adults (EJA), and criterion of accessibility and permanence reached the ratio of 04 participants. We used molecular model, chosen by the subjects (Molecular Visions), such as facilitating the understanding of three-dimensionality of some organic molecules. The development of this study occurred in a total of ten meetings in the auditorium of the CES-Copacabana, where they were treated since the fundamentals of general chemistry ate physiological functions (hydrocarbons: alkanes, alkenes, alkynes, cyclenic or benzene and its derivatives). All meetings were recorded in the form of audio, and analyzed using the method of oral history. After all the meetings and review of the reports occurred, it can be inferred that they have obtained in terms understanding the concepts of organic chemistry, in addition to internalize the concept of the Existence of molecules with three-dimensional features, previously described as incomprehensible. After the use of molecular model, another factor observed during the meetings was the rescue of self-esteem of participants, besides the self-assessment about the opportunities and inclusive socio educational.